2017
DOI: 10.1007/s40544-017-0171-9
|View full text |Cite
|
Sign up to set email alerts
|

Powder metallurgy processed metal-matrix friction materials for space applications

Abstract: Owing to the increasing demand for tribological brakes for space applications, the development of novel materials and advanced technologies is necessary. This paper presents the design, characterization, and realization of powder metallurgy processed metal-matrix friction materials intended for the above-mentioned tribological brakes. Selecting appropriate ingredients, which provides an effective way to tailor the properties of the friction material, is evolving as a strategy to meet the design requirements. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…3) For metal composites, the fabrication methods are mostly similar to those described above. For instance, both powder metallurgy [34] and melt blending are the most popular methods. However, there are some special methods for fabricating metal matrix composites.…”
Section: Preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) For metal composites, the fabrication methods are mostly similar to those described above. For instance, both powder metallurgy [34] and melt blending are the most popular methods. However, there are some special methods for fabricating metal matrix composites.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Besides graphene-based nanocomposites, composites incorporating MoS 2 and BN also exhibit excellent tribological properties. The different types of applications in aviation and aerospace can be categorized into structural components, e.g., fuselages, wings, and moving components, such as bearings, gears, and hatch seals [34]. It is well known that the aviation and aerospace industry depends on many structural and moving machine components; thus, 2DNBCs will play significant roles in this industry.…”
Section: Aviation and Aerospacementioning
confidence: 99%
“…Braking tests of Cu-MMC were performed using a subscale dynamometer (Figure 2a) (MM-3000, Shuntong Institute of Mechanical and Electrical Applied Technology, Xi'an, China) under dry condition at room temperature in air [8]. The dynamic energy was supplied by a flywheel driven by a motor.…”
Section: Braking Testsmentioning
confidence: 99%
“…Çeliktaş et al [7] aimed to produce a reliable and effective aircraft brake lining material and eventually found the most proper ingredient combination of Cu-MMCs. Xiao et al [8] reported the effects of the metal matrix, lubricant component, and friction component on the properties of Cu-MMCs appropriate to space related applications. However, the friction and wear behaviors of brake friction materials are not intrinsic properties and depend on the elements of the particular tribo-system, including the material, braking parameters, and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Powder compaction technology, which is generally called powder metallurgy (PM), has advanced significantly over the past decades [5][6][7][8]. This process can be considered as an alternative, lower cost process compared to other similar metal working technologies and provide cost-effective, but higher quality product [9][10][11].…”
Section: Introductionmentioning
confidence: 99%